UTILIZATION OF THE SIPALAPA APPLICATION INNOVATION IN THE PAMEKASAN PUBLIC LIBRARY - Srirahayu, Dyah Puspita; Firdausi, Amelia; Anugrah, Esti Putri (Publication Library and Information Science, 2024)
The library as a place to accommodate collections, manage and store information should provide quality services for users. The presence of technology makes the library experience changes and creates new innovations for the library. This will have a positive impact on the library itself. If with this innovation the library can have a positive impact both in terms of programs and services provided to its users, then the library will get good feedback. The purpose of this study is to find out how to explain the usability and utilization of the SIPALAPA library application in increasing ease of access to services in the community, to identify the factors that become obstacles in the use of the SIPALAPA application. The research method used is descriptive qualitative method where data is obtained through interviews, observation, and documentation. The results of this study are that the existence of the SIPALAPA application can help libraries provide more optimal services, although there are still some obstacles in launching the application to its development, such as usability in the learnability aspect which still needs assistance and development of library applications to reduce community constraints when utilizing the SIPALAPA application. Barriers to using the SIPALAPA application include: internet network down, application bugs, digital collections that are still limited, lack of socialization and lack of understanding of users facing problems when using the SIPALAPA application. The existence of these innovations must be balanced with the capabilities possessed by librarians because this can affect the services that will be provided to users.